Implementasi Penilaian Kinerja Pegawai Pada Badan Pusat Statistik Karawang - Susilowati, Dela Dwi; Suherman, Enjang (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to identify and understand the employee performance assessment at the Central Bureau of Statistics (BPS) in Karawang. The research employs a descriptive qualitative approach with data collection methods including interviews, observations, and documentation. The findings indicate that the implementation of performance assessments at BPS Karawang is neither significant nor efficient. Despite previous efforts, there are gaps in the assessment that encompass all aspects of employee performance and do not account for external and internal environmental changes. The use of Kip App, a web-based performance assessment tool, aids in planning, monitoring, and evaluating employee performance. The study reveals that the average employee performance scores range from 97-98, indicating a very high level of overall performance. However, some employees have lower scores in the adaptive and harmonious categories, highlighting areas that need further attention.